Environmental Tax Reform and Double Dividend - Roberto Patuelli; Eric Pels; Peter Nijkamp (Tinbergen Institute, 2002)
In this paper we offer a meta-analysis approach to (simulation) studies on environmental tax reform (ETR). The underlying studies look both at environmental effects (e.g. reduction in CO2 emission) and economic effects (e.g. change in gross domestic product) following such a tax reform. The statistical results suggest that the tax type, the recycling-policy and the economic model used in the simulations are all of influence on the chance a double dividend can be obtained. The results are however not entirely conclusive regarding the question which combination of policies and models will lead to a higher double dividend. Our meta-analytic experiment also shows that the specific definition of the double dividend (partly) determines the outcome. These findings should be taken into consideration applying an ETR, to prevent a situation where ETR is rejected or accepted solely due to characteristics of the underlying simulation study rather than the intrinsic ETR itself.
Keywords: H20; Q48; 330; environmental tax reform; double dividend; meta analysis.; Ökosteuer; Steuerreform; Wirtschaftswachstum; Umweltschutz; Theorie; Doppelte Dividende; Meta-Analyse